The Relationship between RIGHT Ethical Behavior Perspective, Demographic Factors, and BEST Ethical Performance - Yamin, Mohammed Ali Yousef (International Review of Management and Marketing, 2019)
Current research aimed the low level of ethical behavior by many university leaders, despite the prevalence of the term ethical leadership in recent years, and determine the Relationship between RIGHT Ethical Behavior Perspective, Demographic Factors, and BEST Ethical Performance. We used the multiple regression analysis to estimate the linear relationship between Best Ethical and Right Ethical, but structural equation modeling was used to test for mediation, the hypothesis that Best Ethical may influence the Best Ethical, through Demographic variables. The surveyed data was analyzed and carried out with STATA 9 software. the study shown that Best Ethical has a positively and significantly effect on the Right Ethical. Also, Best Ethical may affect Demographic variables in terms of an experience only. Gender, Age, and Education seem do not be influenced by Best Ethical since the statistical probability is higher than the significance level. And it is concluded that Gender, Age, and Experience have a positively and significantly effect on Right Ethical, however, Education has a negative and significant effect on Right Ethical. Another important result is that Right Ethical depends on Demographic variables in terms of Age; although, this dependence is no significantly since the statistical probability is higher than the significance level. Keywords: RIGHT Ethical Behavior, Demographic Factors, BEST Ethical Performance. JEL Classifications: M5, M12. DOI: https://doi.org/10.32479/irmm.9100